Respuesta :
Simplify:
−3=12y−5(2y−7)
−3=12y+(−5)(2y)+(−5)(−7)(Distribute)
−3=12y+−10y+35
−3=(12y+−10y)+(35)(Combine Like Terms)
−3=2y+35
Flip the equation.
2y+35=−3
Subtract 35 from both sides.
2y+35−35=−3−35
2y=−38
Divide both sides by 2.
2y/2=−38/2
y=−19
-3 = 12y -5(2y-7)
-3 = 12y +(-5)*2y + (-5)*(-7)
-3 = 12y -10y + 35
-3 = 2y +35
2y= -3 -35
2y = -38
Therefore:
y=-19
As 2*(-19) = -38
-3 = 12y +(-5)*2y + (-5)*(-7)
-3 = 12y -10y + 35
-3 = 2y +35
2y= -3 -35
2y = -38
Therefore:
y=-19
As 2*(-19) = -38
